THE UNITED NATIONS HUMAN RIGHTS COUNCIL’S 2017 REPORT ON FINANCIALIZATION OF HOUSING - Albert Mcbell Ninepence (Journal of Social Political Sciences, 2022)
Financialization of  housing  has  attracted  plenitude of  divergent reviews and discussions  on the subject matter.  The  term  financialization of  housing   has been associated with  reduced  housing affordability in recent  debates.  Irrespective of  financialization of  housing   cementing a springboard to  augment  growth  of the  financial and housing markets,  enhanced employments and  deepened international trade and relations, it has also created its own setbacks. The financialization of housing   has  been reviewed to trigger excessive demerits  of capital gains exceptions, rent seeking  and disregard to upholding  and  defense of human rights tenets, provisions and conventions.  In support of these demerits, the   United  Nations Human Rights Council’s 2017 report on the financialization of housing underscore financialization of  housing  creating  an overall negative impact. The UN reports posits that the finacialization of  housing  is now a means to secure and accumulate  wealth. Housing  is now dehumanized  and sold as a commodity on global markets and hence has lost its currency as a  universal human right.  The copious reviews and contention on the financialization of housing  warrants   further inquiry into the compendious  scholarship. This paper therefore examined and  argued in favour of the  UN standpoints though making counter  perspectives on the discourse of financialization of housing.